Demografski trendi in medgeneracijska solidarnost v pokojninskem zavarovanju - Rangus, Andraž (Delavci in delodajalci, 2022)
Demographic changes and the ageing of the population are causing strong fiscal pressures on financing of the systems of social security, especially on the systems of pension insurance. The reform processes of these systems must be executed cautiously and first of all in line with the principles of the type of the welfare state into which the individual state is classified. Slovenia, which has one of the worst demographic pictures, will in the near future have to implement a more comprehensive reform that will make the pension system more intergenerationally fair and acceptable.
Keywords: demografija; demography; intergenerational solidarity; medgeneracijska solidarnost; pension system; pokojninska reforma; pokojninski sistemi; pokojninsko zavarovanje; upokojenci